Computational Capacity Planning for Running Multiplayer Games on Cloud and Fog Infrastructures - Alves, Melissa; Wanderlei, Jose; Barbosa, Vandirleya; Sabino, Arthur; Lima, Luiz Nelson; Feitosa, Leonel; Clua, Esteban; Silva, Francisco Airton (Anais do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames); 2025: Anais do XXIV Simpósio Brasileiro de Jogos e Entretenimento DigitalDO - 10.5753/sbgames.2025.9829, 2025)
Introduction: Data traffic in multiplayer games consists of realtime exchanges of commands between servers and players’ devices, which demand an immediate response. As the data volume increases, the system becomes overloaded, resulting in high latency and packet loss. Objective: This work proposes a new Stochastic Petri Net (SPN) model to evaluate the performance of this traffic in Fog–Cloud architectures designed for large-scale multiplayer games. Methodology: We built a SPN model and validated a simplified version; the model computes utilization, mean response time, drop probability, and throughput, allowing us to analyze the impact of different capacity configurations and load-distribution strategies. Results: The results reveal a direct relationship among processing capacity, load balancing, and quality of service: increasing the number of cloud GPUs reduces latency and packet loss while boosting throughput.